2018
DOI: 10.9734/jammr/2018/33827
|View full text |Cite
|
Sign up to set email alerts
|

Childhood Urinary Tract Infection: Clinical & Laboratory Profile in a Tertiary Care Hospital of Bangladesh

Abstract: Background: Urinary Tract Infection (UTI) implies presence of actively multiplying organisms in the urinary tract. Although it is infrequently associated with mortality, it is still an important cause of morbidity in the paediatric age group. Prompt diagnosis and early initiation of appropriate antibiotics in children reduce the morbidities associated with UTI. Objective: This study was undertaken to observe the clinical and laboratory profile of UTI in children attending outpatient department (OPD) of Combine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 14 publications
(44 reference statements)
0
4
0
Order By: Relevance
“…This result corresponds to other study. 11,12 In the present study the most common presentation was fever, followed by urinary complaints, vomiting, abdominal pain & others (Table II). Similar result was found in a study done in Bangladesh & other countries.…”
Section: Discussionmentioning
confidence: 48%
See 2 more Smart Citations
“…This result corresponds to other study. 11,12 In the present study the most common presentation was fever, followed by urinary complaints, vomiting, abdominal pain & others (Table II). Similar result was found in a study done in Bangladesh & other countries.…”
Section: Discussionmentioning
confidence: 48%
“…This corresponds with the data obtained by other investigators. 12,16 Klebsiella was the second most uropathogen in our study. Similar result was shown by a study done by Haghi-Ashteiani et al 17 But Sharma Gaurav et al showed Staphylococcus as.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…Isolation of causative organism in urine culture is considered confirmatory with a colony count of >1,00,000 cfu/ml in midstream urine in females and >10,000 cfu/ ml in males respectively. A growth of single species of bacterial pathogen with colony count of ≥100 cfu/ml from a sample obtained by urinary catheterization or any growth of bacterial pathogens in a sample collected by suprapubic aspiration constitutes significant bacteriuria 7,8,9,10 Over the years there has been an emerging trend of resistance to antibiotics which are used as an antibacterial agent. It is important to know the type of uropathogens in the locality and their resistance pattern to commonly used antimicrobials.…”
Section: Introductionmentioning
confidence: 99%